Monitoring Karyawan Dengan Metode LBS (Location Based Service) Berbasis Android Pada PT Perkebunan Nusantara VI Jambi – Sumatra Barat - Nugraha, Alen Abdi; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2022)
PT Perkebunan Nusantara VI is one of the companies operating in the plantation sector that is transforming the development of information technology to improve the efficiency and effectiveness of the company. PT Perkebunan Nusantara VI has an HR Department which is implementing changes to business processes that were originally monitoring employees including for attendance, leave permits and leave are recorded manually. In Monitoring employees manually, there are many obstacles to reporting caused by the monitoring process not being carried out in real time. Based on these conditions, a system is needed that can assist in monitoring employee activities both from attendance, exit permits and integrated leave. With an android-based application and web dashboard, the process of monitoring employees in each Business Unit at PT Perkebunan Nusantara VI can be done in real time and also assists in the reporting system. So the final result of this research is the proposed employee monitoring application with themethod location based service which can greatly assist the HR Department in monitoring employees and reporting that is integrated in real time.